Penerapan pembelajaran kooperatif tipe think talk write (TTW) untuk meningkatkan keterampilan menulis kembali teks narasi pada peserta didik kelas IV sekolah dasar - Puput Nur Wijayanto; Rukayah Rukayah; Tri Budiharto (Universitas Sebelas Maret, 2020)
Abstract. This research aims are: 1) to improve writing skills again through the application of cooperative learning in the type of think talk write, and 2) to describe the results of the application of cooperative learning in the type of think talk write. This research is a class action research with two cycles. The subjects of this study were 4th grade students at Karangasem III Elementary School Surakarta in the academic year 2019/2020, totaling 31 students. This study uses data collection techniques in the form of interviews, observation, documentation analysis and tests with content validity data analysis, technical triangulation and source triangulation. Analysis of the data used is describing comparative analysis and Miles-Huberman interactive analysis models. The conclusion is that the writing skills of the 4th grade students at Karangasem III Elementary School in Surakarta in the academic year 2019/2020 can be improved through cooperative learning in the type of think talk write. The results of this study have contributed to the world of education as an alternative to solving the psychomotor domain, namely the ability to rewrite narrative textsKeywords: cooperative learning the type of think talk write, writing skills, primary school